The use of viticultural terroir units for demarcation of geographical indications for wine production in Stellenbosch and surrounds - Carey, Victoria Anne (Stellenbosch : Stellenbosch University, 2012)
Dissertation (PhD(Agric)) -- Stellenbosch University, 2005.